Co-isolation of genetically distinct Burkholderia pseudomallei strains from a single patient in North Queensland - Pauline M. L. Coulon; Piklu Roy Chowdhury; Ian Gassiep; Kay Ramsay; Aven Lee; Edita Ritmejeryte; Miranda E. Pitt; Joyce To; Sarah Reed; Patrick N. A. Harris; Garry S. A. Myers (PLoS ONE, 2025)
While investigating colony morphology variation within clinical isolates of Burkholderia pseudomallei ( Bp) isolated from a single clinical infection, we identified two distinct strains (based on their multi-locus sequence type) from Bp TSV292. Reports of simultaneous co-infection are un-common, with only two studies in Thailand documenting such cases: (1) 2 out of 133 cases, and (2) 13 out of 59 patients infected with two to three polyclonal Bp strains exhibiting different genotypes. Here, we present the first comprehensive multi-omics characterization of co-infecting Bp strains isolated from a single infection at a hospital in Townsville, Australia, in 2018. This finding impacts the design of future diagnosis and treatment of Bp .